The 'Holy Trinity' of Methodological Rigor: A Skeptical View - Chris L. S. Coryn (The Evaluation Center at Western Michigan University, 2007)
Rigor in research is normally conceived of as the means by which integrity and competence are confirmed (Tobin & Begley, 2004).1 That is, a way of demonstrating the legitimacy or soundness of the research process. Without rigor, it is argued, there is a danger that research may become fictional journalism and therefore worthless as contributing to knowledge (Morse, Barrett, Mayan, Olson, & Spiers, 2002).